2022
DOI: 10.1021/acsanm.2c00446
|View full text |Cite
|
Sign up to set email alerts
|

S-Scheme Bi2S3/CdS Nanorod Heterojunction Photocatalysts with Improved Carrier Separation and Redox Capacity for Pollutant Removal

Abstract: Constructing step scheme (S-scheme) heterojunctions makes it possible for promoting the separation and transfer of photoinduced carriers, as well as maintaining strong photoredox capacities. Herein, S-scheme Bi 2 S 3 /CdS heterojunctions were designed and constructed by the in situ substitution of Bi 3+ on CdS nanorods. The Sscheme 10%-Bi 2 S 3 /CdS heterojunction with intense interfacial contacts shows not only an optimal photoreduction rate toward Cr(VI) (3.18 and 7 times that of pure CdS and Bi 2 S 3 , resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The band gap of the photocatalyst can be evaluated according to the following equation: 38 αhν = A ( hν − E g ) n /2 where α (proportional to A ) is the absorption factor, ν refers to the light frequency, E g means the band gap, and h represents Planck's constant. 10 n is 1 and 4 for CdS and g-C 3 N 5 . 39,40 The value of n represents the type of semiconductor, 1 is for direct transition and 4 is for indirect transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band gap of the photocatalyst can be evaluated according to the following equation: 38 αhν = A ( hν − E g ) n /2 where α (proportional to A ) is the absorption factor, ν refers to the light frequency, E g means the band gap, and h represents Planck's constant. 10 n is 1 and 4 for CdS and g-C 3 N 5 . 39,40 The value of n represents the type of semiconductor, 1 is for direct transition and 4 is for indirect transition.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 However, the fast recombination rate of electron-hole (e + /h + ) pairs and severe photocorrosion have limited the application of CdS. 10 Numerous strategies such as structural/morphological modifications, band gap alterations, co-catalyst and surface sensitizations have been attempted to improve the photoconversion efficiency of CdS. 11 It was found that the construction of heterojunctions could promote the separation of photogenerated charges and prolong the service life.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration was 20 mg L À1 , fewer intermediates were produced and less likely to compete with RhB ions for the photogenerated electrons, thus becoming the optimal degradation concentration. 51 The degradation of the C-Ti(I/S)-3 composite at different pH values was tested (Fig. 8(b)), and it was found that acidic conditions led to enhanced degradation, which may be due to the increased adsorption.…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…For the past few years, the detriment of organic pollutants to the water environment has become more and more serious, and has caused widespread concern. 1 Utilizing semiconductor photocatalysis technology to remove organic pollutants has been greatly developed, especially the research and application of narrow-band gap semiconductor photocatalysts absorbing UV− visible light. 2 Silver phosphate (Ag 3 PO 4 ), owing to a narrow band gap, could seize light sources less than 530 nm, and the photogenerated carriers can be efficiently separated because PO 4 3− itself has a large negative charge to refuse electrons.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, the detriment of organic pollutants to the water environment has become more and more serious, and has caused widespread concern . Utilizing semiconductor photocatalysis technology to remove organic pollutants has been greatly developed, especially the research and application of narrow-band gap semiconductor photocatalysts absorbing UV–visible light .…”
Section: Introductionmentioning
confidence: 99%